Perfil químico, atividade anti-inflamatória e antioxidante das cascas dos frutos de Libidibia ferrea - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
Libidibia ferrea is a medium-sized tree known as jucá, found in the North and Northeast of Brazil. The use of various parts of the tree is very common in folk medicine, especially in the distant regions of large urban centers. Jucá fruits are used in the form of tea or decoction to prevent or treat inflammation. The fruits were collected in the urban area of the City of Manaus / Amazonas. After grinding, 300 g of jucá powder were extracted by maceration with methanol for five days to obtain the crude extract. The analyzes in HPLC-MS were performed on crude metanolic extract of juca fruit peels and crude hydrolyzed extract. Some hydrolysable tannins, HHDP acid, DHHDP acid and chlorogenic acid were identified. The crude extract was subjected to a liquid-liquid partition, to give the phases in hexane, chloroform, ethyl acetate and hydroalcoholic phase. Tests of antioxidant activity (DPPH and ABTS) and anti-inflammatory (LOX) were performed in the phases obtained. The ethyl acetate phase was more effective in all the tests (IC50 DPPH = 3.32, IC50 ABTS = 4.12, IC50 LOX = 8.62), while the hexane phase presented the worst results among the fractions (IC50 DPPH = 59.92, IC50 ABTS = 211.37, IC50 LOX = 140.45). The AcOEt phase was subjected to column chromatography using Sephadex LH-20 and methanol as the mobile phase. The resulting AcS2 fraction was fractionated in Sephadex LH-20 again using methanol as the mobile phase, whose AcSS2 fraction was subjected to solid phase extraction using as the mobile phase H2O/ACN mixtures. All fractions were analyzed in analytical HPLC and fractions 6 and 7 were pooled and ellagic acid and methoxygeraniine were identified, the elucidation of the substances occurred by negative-mode EM-NMR and NMR (MeOD, 500 MHz). Finally, antioxidant activity assays were performed for ellagic acid (IC50 DPPH = 49.57, IC50 ABTS = 60.00) and methoxygeraniine (IC50 DPPH = 8.59, IC50 ABTS = 6.49). The isolation method present in this work can be used to obtain other substances with antioxidant and anti-inflammatory activity and also for the quantification of these substances.
Keywords: Libidibia ferrea; Lipo-oxigenase; Substâncias fenólicas; Ácidos fenólicos; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA